2018
DOI: 10.1080/16000889.2018.1468704
|View full text |Cite
|
Sign up to set email alerts
|

The impact of future atmospheric circulation changes over the Euro-Atlantic sector on urban PM<sub>2.5</sub> concentrations

Abstract: Air quality management is strongly driven by legislative aspects related to the exceedance of air quality limit values. Here, we use the Norwegian Climate Centre's Earth System Model to assess the impact of a future scenario of maximum feasible aerosol emission abatement and increasing greenhouse gases (RCP4.5) on urban PM 2.5 concentrations in Europe. Daily PM 2.5 concentrations are assessed using a novel downscaling method which allows us to compute exceedances of current and planned air quality thresholds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Both PM2.5 and PNC had a monotonic downward trend while long-term measurements of temperature, precipitation, and wind speed had no particular trend. Additionally, the increasing intensity and frequency of climate variabilities causing extreme events due to changing climates also influenced PM concentrations (Jeong et al, 2018;Markakis et al, 2016;Messori et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both PM2.5 and PNC had a monotonic downward trend while long-term measurements of temperature, precipitation, and wind speed had no particular trend. Additionally, the increasing intensity and frequency of climate variabilities causing extreme events due to changing climates also influenced PM concentrations (Jeong et al, 2018;Markakis et al, 2016;Messori et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Both anomalies in the polarfront jet and merged flow episodes can favour a range of surface extremes in Europe, for example in precipitation, temperature, surface wind or particular matter concentrations [e.g. 8,[10][11][12][13][14][15]. A parallel stream of literature has focused on linking planetary waves to surface extremes [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Climate model simulations have suggested that southern Europe is likely to experience a higher incidence of positive North Atlantic Oscillation states in the future and a large eastward shift of both North Atlantic sea‐level pressure centres of action, combined with more frequent mid‐latitude blocking and a northward shift of the jet stream. All these atmospheric circulation changes would increase the frequency of stagnant air masses over urban centres and the consequent degradation of air quality, increasing the PM 2.5 concentrations beyond the World Health Organization Air Quality Guidelines (Messori et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%